What Will People Think? How College Students Evaluate Bystander Intervention Behavior - Clay-Warner, Jody (Journal of interpersonal violence, 2025)
Many colleges utilize bystander intervention programs to address gender-based violence. The goal of these programs is to help students overcome barriers to intervention, including evaluation inhibition, which occurs when bystanders expect to be viewed negatively for intervening. We have limited information, though, on how college students evaluate bystanders who intervene. Specifically, we do not know whether evaluations of bystanders who engage in different levels of intervention vary across situations or how men and women who intervene similarly are evaluated. Without this information, it is difficult to design prevention programs that help bystanders overcome evaluation inhibition. To gather this information, we conducted a vignette experiment with college student participants (n = 82). We specifically examined how students evaluated the reasonableness of male and female bystanders who engaged in different behaviors (direct intervention and threatening to tell an authority, direct intervention only, indirect intervention, doing nothing) across four situations (assault at a party, workplace harassment, harassment by a teaching assistant, and intimate partner violence). Analyses of variance found that there was situational variability in how the bystander is evaluated for different intervention tactics, though bystanders who did nothing were always evaluated the most negatively. Bystander’s gender, however, did not affect evaluations, suggesting that intervention expectations for men and women are similar. These results indicate that while there is an underlying norm supportive of intervention behavior, situational characteristics influence whether college students think it is reasonable to call authorities, confront the perpetrator, or engage in indirect intervention. The central implication of this study is that bystander intervention training should provide opportunities for students to practice intervention behaviors across a wide variety of situations of gender-based violence in order build up their store of intervention tactics, thus increasing their ability to overcome evaluation inhibition.